2019
DOI: 10.1111/1751-2980.12825
|View full text |Cite
|
Sign up to set email alerts
|

Colonic mucosa‐associated candida assessed by biopsy culture is associated with disease severity in ulcerative colitis: A prospective study

Abstract: Objective: To evaluate the relationship of mucosa-associated candida (MAC) and disease severity in patients with ulcerative colitis (UC).Methods: We prospectively investigated the presence, nature, and quantification of MAC in patients with UC and its relationship with disease severity. Consecutive patients with UC were assessed for clinical, endoscopic, histological features and serum markers of disease severity. All patients underwent mucosal brushing cytology, brushing culture, and biopsy culture for candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…It is likely to colonize the mucosal defects and further perpetuates the inflammation 14. In our previous study, we found that mucosa associated Candida was associated with increase in disease severity and mucosal inflammation 6. In quantitative mucosa biopsy cultures, patients with UC had higher Candida colony counts (≥10 3 CFU/mL) than controls.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…It is likely to colonize the mucosal defects and further perpetuates the inflammation 14. In our previous study, we found that mucosa associated Candida was associated with increase in disease severity and mucosal inflammation 6. In quantitative mucosa biopsy cultures, patients with UC had higher Candida colony counts (≥10 3 CFU/mL) than controls.…”
Section: Discussionmentioning
confidence: 92%
“…In quantitative mucosa biopsy cultures, patients with UC had higher Candida colony counts (≥10 3 CFU/mL) than controls. The species of Candida isolated were C. albicans , Candida tropicalis , Candida metapsilosis , Candida parapsilosis , Candida lustinaie , and Candida glabrata 6 . Candida is known to inhibit mucosal immunity and promote mucosal inflammation 26,27.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Numbers of Bacteroides and Candida have been observed to significantly increase in feces of patients with UC. 25,26 Another analysis has reported that less butyrate is synthesized by Clostridium in the luminal flora of patients with UC, suggesting a protective role of Clostridium in the initiation of UC. 27 Moreover, a fecal metabolomics study further revealed an increased frequency of symbiotic Escherichia coli during intestinal inflammation, and its respiration and formate oxidation have been proved to participate in the occurrence of microbial imbalance and intestinal inflammatory response.…”
Section: Unique Microbial Signatures In Ibdmentioning
confidence: 99%